Risk of Renal Cell Carcinoma Associated with Calcium Channel Blockers: A Nationwide Observational Study Focusing on Confounding by Indication. Issue 6 (November 2020) - Kristensen, Kasper Bruun; Habel, Laurel A.; Gagne, Joshua J.; Friis, Søren; Andersen, Klaus Kaae; Hallas, Jesper; Pottegård, Anton
Abstract : Background: We examined whether the apparent association between renal cell carcinoma (RCC) and use of dihydropyridine calcium channel blockers (CCBs) was explained by confounding by indication since hypertension, the main indication for CCBs, is a risk factor for RCC. Methods: Using Danish health registries, we conducted a nested case-control study including 7315 RCC cases during 2000–2015. We matched each case with up to 20 controls on age and sex using risk-set sampling. We estimated odds ratios (ORs) for long-term CCB use associated with RCC using conditional logistic regression. We addressed confounding by indication by (1) adjusting for hypertension severity indicators; (2) evaluating dose-response patterns; (3) examining whether other first-line anti-hypertensives were associated with RCC; and (4) using an active comparator new user design by nesting the study in new users of CCBs or angiotensin-converting enzyme inhibitors (ACEIs). Results: The adjusted OR for RCC associated with long-term CCB use compared to non-use was 1.76 (1.63–1.90). After we additionally adjusted for hypertension severity indicators, the OR remained elevated (OR 1.37; confidence interval [CI] 1.25, 1.49) with evidence of a dose-response pattern. Other anti-hypertensives were also associated with RCC, for example, ACEIs (OR 1.27; 95% CI = 1.16, 1.39) and thiazides (OR 1.22; 95% CI = 1.12, 1.34). In the active comparator new user design, the OR was 1.21 (95% CI = 0.95, 1.53) for use of CCBs compared with ACEIs. Conclusions: In this population, confounding by indication appeared to explain at least part of the association between RCC and dihydropyridine CCBs. Abstract : Supplemental Digital Content is available in the text.